Специфіка здійснення реформи децентралізації в регіонах України: здобутки і прорахунки - Бевз, Т. (Народна творчість та етнологія, 2019)
Децентралізація в Україні визначена як національний пріоритет. Завдяки децентралізації громадяни матимуть можливість самостійно вирішувати свої проблеми. Децентралізація важлива ще й тому, що вона покликана змінити спосіб мислення, поведінки людей та стати ефективним інструментом економічного, інфраструктурного та соціального розвитку. Розглянуто вплив центральної влади на процеси децентралізації в регіонах, з одного боку, та мовчазне спостереження або навіть саботаж, недовіру, невіру, а іноді й прямий опір з боку керівників регіональних та районних органів представницької та виконавчої влади, з іншого. Аналізуються проблеми конфігурації громад. Decentralization in Ukraine is defined as a national priority. Due to decentralization, citizens will have an opportunity to solve their problems independently. Decentralization is also important because it is intended to change the way people think and behave, and become an effective instrument of economic, infrastructural, and social development. An influence of the central government on the processes of decentralization in the regions, on the one hand, and silent observation or even sabotage, distrust, unbelief, and sometimes direct opposition from the part of heads of regional and district bodies of representative and executive power, on the other, are considered. Problems of community configuration are analyzed; model: one district, one community, radical changes in many spheres of life of the United Territorial Communities: positive and negative experience. There are some trends in the activities of the United Territorial Communities: those communes that have been created earlier focus on increasing the revenue side of their budgets, deciding how to augment budgets in the future, developing businesses, and newly created communities invest in solving urgent problems. The greatest opposition to decentralization by regional state administrations is observed in Kyiv, Sumy, Transcarpathian, and Odesa oblasts. Particular attention is paid to the situation in the United Territorial Communities of Donetsk and Luhansk regions.